New CAP Delivery Model, Old Issues - Marko Lovec; Tanja Šumrada; Emil Erjavec (Intereconomics, 2020)
The proposed Common Agricultural Policy (CAP) for the period 2021–2027 will be more flexible and, presumably, more effective. To provide for sufficient ambition and prevent a race to the bottom, national strategic plans will be introduced with quantitative targets covering both policy pillars. This article argues that since formal requirements and the evaluation model are weak on actual long-term impact, substantial improvements are unlikely. To test this, programming rules are experimentally evaluated on the implementation of CAP 2014–2020 in Slovenia. The experiment shows that while measures and resources broadly correspond to policy objectives, the specific relevance of measures is generally weak and has potential effects dispersed among several objectives, resulting in high costs for individual objectives at best. Without the effective inclusion of an impact assessment, the outcome will rely on the capacity and benevolence of national governance systems.
Keywords: 330